DETERMINATION OF VACCINATION RULE BASED ON NAJIS(IMPURITIES) NOTION ACCORDING TO ISLAM AND SCIENCE IN MALAYSIA - Kashim, Mohd Izhar AriffMohd; Mohamad, Mohd Nasran; Hasim, Nur Asmadayana; Yahaya, Mohammad Zaini; Safri, Lenny Suryani; Mokhtar, Mohd Helmy (The journal of contemporary issues in business and government, 2021)
The spread of diseases prompted by dangerous viruses harms all walks of life, regardless of age or gender. The spread of these diseases is more likely to infect children, and it worsens the situation. The level of immunity of children is lower than that of adults due to their immature immune system and is still building resistance and immunity to disease attacks. In an attempt to overcome this problem, global doctors introduced vaccines to strengthen the human body’s immunity further to cope with various infectious diseases. Nevertheless, there is a group of anti-vaccines, particularly among Muslims who rejected vaccines because they are derived from najis (impurities). The allegation garnered attention from certain groups based on religious beliefs. Hence, this research’s objective was to study the fatwa determination of vaccine rule derived from najisaccording to Islamic perspective and analyse scientific views more clearly about vaccines. This study adopted a descriptive qualitative method of literature review and document analysis. The research outcomes revealed that, from an Islamic perspective, the use of najis-derived vaccines are required, and it is in line with Maqasid al- Syariah’s requirements. The use of vaccines is categorised in the emergency category, while the production of 100% halal vaccines in the future can be produced and used. The scientific perspective also establishes the need to use this vaccine to control infectious diseases and maintain universal human health.